Serum enzyme profile during gestation and early lactation in Gir and crossbred cows* - Ingole, S D; Talvelkar, B A; Deshmukh, B T; Nagvekar, A S (The Indian Journal of Animal Sciences, 2012)
SGOT, SGPT, AKP, LDH and ChE were estimated in Gir and crossbred cows during pregnancy and early lactation period. The SGOT levels showed highly significant difference between the groups in both the breeds. The values showed significant decrease with the advancement of gestation. The SGOT activity was also higher in early lactating cows. The SGPT levels indicated highly significant difference between groups in Gir cows and significant difference in crossbred cows. The difference in serum AKP levels between groups was significant in both the breeds. Serum LDH values between the groups differed significantly in Gir cows and crossbred cows. The LDH activity was higher during estrus, then decreased at early gestation and then it increased up to parturition and again decreased in early lactation period. The difference in serum ChE levels between the groups was highly significant in Gir and crossbred cows. A decreasing trend in serum ChE levels was observed in Gir from estrus to late pregnancy.